O simulacro da conversação no Jornal Nacional - Ferraz, Patrícia (2017)
In April 2015, Jornal Nacional, from TV Globo, suffered a general reformulation which have transformed the verbal language, besides other aspects. The informality in the new TV show seemed evident. However, has the verbal language been able to establish a genuine conversation between the journalists? While recognizing the need of an interdisciplinary approach to the theme, we seek the theoretical framework to this research inside three distinct areas. Supported by Marcuschi, Koch, Fávero and Chafe, we compare the discourses from 2011 and 2015, trying to situate them in the oral x literate continuum. Within the Conversation Analysis approach, we analyze the discourses seeking interactionists Discursive Markers. After a theoretical review about journalistic objectivity, we investigate the reformulation influence on the objectivity strategies adopted in these two periods, in order to understand how the changes fosters the newscast emotionality. The research demonstrates that the conversational purpose, which is the basis for the verbal reformulation, is not accomplished. Discourse Analysis provides the understanding that this is a fake conversation, raised in order to seduce the audience, which is considered as an affective target. Despite the numerous and regular studies about Jornal Nacional, none of them had already explored the relation between informality strategies and the pursuit of interaction